Using of the simplified solutions of the problem of Stefan at designing of ray auxiliaries - Ju. A. Samoilovich; V. I. Timoshpolski; G. A. Klimovich (Литьë и металлургия)
In the article there is examined the problem of application of the conformal maps method at the projection of the foundry processes auxiliaries. There is given the solution of the problem of Stefan for more typical configurations of design field at projection of discard heads and outside chiller.